Synthesis and fabrication of a thin film containing silica-encapsulated face-centered tetragonal FePt nanoparticles - Yu, C; Caiulo, N; Lo, C; Tam, K; Tsang, S (2006)
A thin film containing silica encapsulated face-centered tetragonal FePt nanoparticles was synthesized by using sequential nanochemistry preparation techniques. The silica coating offered the alloy particles a physical barrier against sintering by modifying their diffusion rates and surface energies during the high-temperature annealing required for the fct phase transition. It was found that each quasi-spherical silica particle embracing the FePt can undergo self-assembly into a closely packed, ordered 2D array structure with identical interparticle spacing on a thin supporting film. A strong chemical attachment of the silica nanosphere to the oxide film was evident through a surface dehydroxylation reaction. A Langmuir-Blodgett (LB) deposition technique to control the arrangement of the silica encapsulated FePt on a substrate was carried out, followed by a high-temperature heat treatment and the heat-treated, silica-encapsulated sample displays magnetic hysteresis.